The Open Access in the Context of the Globalizing World - Koutras, Nikos (2015)
Globalization and the internet are intrinsically linked. This obvious fact has major implications for how the publishing industry will be modified in the foreseeable future. This change may be technologically driven but there is a place for intellectual debate about the appropriate regulation of the field. This requires an examination of the commercial and moral claims of the authors or creators and the conventional publishers vis a vis those of the end users both nationally and internationally. This analysis will enable me to make an argument about the importance of open access as an appropriate governance mechanism for both protection and distribution of information in the international arena. In addition, this paper argues that in a globalized world justice and social cohesion requires commercial Multinational corporations (MNCs) to act responsibly and ethically. Most of the big publishing houses are such MNCs and if open access repositories (OARs) are to be relevant such publishing houses will have to embrace the concept. Overall, I will use the concept of corporate social responsibility to make the argument that it is logical and feasible that publishing MNCs can modify their business practices and adopt OARs.